ANALISIS KINERJA PELAKSANAAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) PEMERINTAH KABUPATEN TANA TORAJA - Bonilisa Rantebalik Tawakkal; Anna Sutrisna S (Tirtayasa Ekonomika, 2016)
Abstrack This research was conducted to analyze the implementation performance Regional Revenues and Expenditures Budget of Tana Toraja sLocal Government during the 2010-2014 period with three performace approach consist of Revenues, Expenditures, and Financing. Analyze method used in this research is descriptive with qualitative approach and quantitative approach.The results showed that the performance of Regional Revenues and Expenditures Budget Tana TorajaLocal Government during the 2010-2014 period generally is quite good.The Budget performance based on revenues approach is good with positive revenues growth and local real revenues during the 2010-2014 period could realized more than the expectation which is covered on budget. The Budget performance based on expenditures approach, there are some programs which is not realized maximal, besides that the allocation of budget utilization focused on goverment daily activity. Based on Fincing sector, showed that positive performance of SILPA growth so it means that appropriately budget presentation by local government.Keyword: Regional revenues and expenditures budget, regional revenues and expenditures, SILPA.